PELAKSANAAN PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) TERHADAP TANAH-TANAH YANG BELUM BERSERTIFIKAT HAK MILIK (SHM) DALAM RANGKA KEPASTIAN HAK ATAS TANAH DI KABUPATEN PATI - Purbaningsih, Lela Arumsari (Jurnal Suara Keadilan, 2023)
The implementattion of the PTSL Program carries out by the Pati Regency Land Office received an enthusiastic from the community whose lands had not yet been certified. There is a lot public interest in wanting to take part in the PTSL program is funded by the goverment or the state and the process is also very fast when compared to independent certificates. Howover, there are also some community members who do not want to join the PTSL program for their own reasons. The costs for the PTSL program are indeed funded by the goverment or the state, but the community is still charged a fee because in accordance with applicable regulations according to Pati Regent Regulation Number 1 of 2021 it is stated that PTSL applications are still burdened with a fee of Rp.150.000,- to Rp.400.000,-. This is borne by the applicant in order to finance or buy stakes, stamp duty,committe fees, office stationery and transportation for village committe officers. The imposition of fees as mentioned above had previously been socialized to the villagers by the PTSL comitte.